(untitled) (Journal of actual problems of jurisprudence, 2018)
The article considers the issues of state regulation in the healthcare sector. We consider the legal framework in the field of health care associated with changes in the current legislation. Features of legal maintenance of public relations in the field of medical activity, due primarily, the need to improve the national legislation regulating relations in the sphere of public health protection. Key words: government regulation, mechanism of administrative and legal regulation, healthcare system, health care, medical law.